Spaces in Architecture : Areas, Distances, Dimensions - Bielefeld, Bert (Birkhäuser, 2019)
The design of a building is a complex process in which the architect develops spaces which are defined by a number of different parameters. The most important of these are space requirements, distances, furniture and fittings, and movement zones. From the dimensions of the human body it is possible to derive guide values for these reference sizes that make spaces comfortable to be in and to use. Spaces in Architecture is a useful reference work for students and designers for quickly looking up detailed information on space scenarios that occur in many different types of buildings. For example, the book lists all important dimensions for entrance areas, doors, staircases, ramps, and elevators. On the basis of this fundamental information it is possible to design buildings in terms of function and type.